PENDIDIKAN KARAKTER MELALUI KEGIATAN KEAGAMAAN DI SMA IT RAFLESIA DEPOK - Maulana, Irwan (Fakultas Keguruan dan Ilmu Pendidikan Universitas Faletehan, 2023)
SMA IT Raflesia Bogor is a school that implements character education through daily, weekly, monthly and yearly programs so as to contribute to advancing a nation. The purpose of this research is to describe the phenomenon of character education through religious activities at SMA IT Raflesia. This study uses a qualitative approach using data collection techniques, namely observation to observe phenomena in the field, interviews are used to interview school principals, students, curriculum, IRMA coaches, and several students X and XI and parents. Data processing uses data reduction, data presentation, and drawing conclusions. The results of this study are that SMA IT Raflesia implements character education in three ways, namely daily, weekly, monthly and yearly. Meanwhile, daily includes (1) praying five times a day; (2) duha prayer; (3) greet teacher and sesame; (4) pray before and after studying. There is also violence, namely the study on Thursday. Annual activities through commemoration of Islamic holidays (PHBI).